Is there a causal relationship between acute stage sensorimotor cortex activity and the development of chronic low back pain? a protocol and statistical analysis plan. Issue 12 (29th December 2019) - Jenkins, Luke; Chang, Wei-ju; Buscemi, Valentina; Cunningham, Chelsea; Cashin, Aidan; McAuley, James H; Liston, Matthew; Schabrun, Siobhan M
Abstract : Introduction: Why some people develop chronic pain following an acute episode of low back pain is unknown. Recent cross-sectional studies have suggested a relationship between aberrant sensorimotor cortex activity and pain persistence. The UPWaRD (Understanding persistent Pain Where it ResiDes) cohort study is the first prospective, longitudinal investigation of sensorimotor cortex activity in low back pain. This paper describes the development of a causal model and statistical analysis plan for investigating the causal effect of sensorimotor cortex activity on the development of chronic low back pain. Methods and analysis: Sensorimotor cortex activity was assessed within 6 weeks of low back pain onset using somatosensory evoked potentials and transcranial magnetic stimulation mapping techniques. Chronic low back pain is defined as ongoing pain (Numerical Rating score ≥1) or disability (Roland Morris Disability Questionnaire score ≥3) at 6 months follow-up. Variables that could confound the relationship between sensorimotor cortex activity and chronic low back pain were identified using a directed acyclic graph and content expertise was used to specify known causal paths. The statistical model was developed 'a priori' to control for confounding variables identified in the directed acyclic graph, allowing an unbiased estimate of the causal effect of sensorimotor activity in acute low back pain on the development of chronic pain. The statistical analysis plan was finalised prior to follow-up of all participants and initiation of analysis. Ethics and dissemination: Ethical approval has been obtained from Western Sydney University Human Research Ethics Committee (H10465) and from Neuroscience Research Australia (SSA: 16/002). Dissemination will occur through presentations at national and international conferences and publications in international peer-reviewed journals. Trial registration number: ACTRN12619000002189 (retrospectively registered)